2004
DOI: 10.1021/bi035820d
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of the C-Terminus of the ε Subunit from the Chloroplast ATP Synthase

Abstract: The ATP synthases from chloroplasts and Escherichia coli are regulated by several factors, one of which is the epsilon subunit. This small subunit is also required for ATP synthesis. Thylakoid membranes reconstituted with CF1 lacking the epsilon subunit (CF1-epsilon) exhibit no ATP synthesis and very high ATP hydrolysis. Either native or recombinant epsilon restores ATP synthesis and inhibits ATP hydrolysis. Previously, we showed that truncated epsilon, lacking the last 45 C-terminal amino acids, restored ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…The other subunit in this interaction remains to be identified, but, on the basis of previous studies, the DELSEED region of the ␤ subunit seems a likely possibility (12). Studies with the chloroplast ATP synthase have shown that the C-terminal domain of the ε subunit is a regulator of ATP hydrolysis activity both in CF 1 and CF 1 F o , and most of this inhibitory activity can be attributed to the last 45 C-terminal amino acids (38,39). While the ε subunit is a regulator of ATP hydrolysis activity, ATP synthesis experiments revealed that the C-terminal domain of the ε subunit is not required for photophosphorylation (39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other subunit in this interaction remains to be identified, but, on the basis of previous studies, the DELSEED region of the ␤ subunit seems a likely possibility (12). Studies with the chloroplast ATP synthase have shown that the C-terminal domain of the ε subunit is a regulator of ATP hydrolysis activity both in CF 1 and CF 1 F o , and most of this inhibitory activity can be attributed to the last 45 C-terminal amino acids (38,39). While the ε subunit is a regulator of ATP hydrolysis activity, ATP synthesis experiments revealed that the C-terminal domain of the ε subunit is not required for photophosphorylation (39).…”
Section: Resultsmentioning
confidence: 99%
“…ATPase activity of the chloroplast F 1 F o -ATP synthase (CF 1 F o ) is subject to complex regulation to prevent wasteful ATP hydrolysis under dark conditions. Under such conditions, the enzyme is inhibited by Mg 2ϩ -ADP (8), the ε subunit (38,39,42), and the oxidation/reduction state of the ␥ disulfide bond (37). Exposure of thylakoid membranes to light results in the generation of a ⌬ H ϩ that stimulates the release of inhibitory bound ADP and relieves inhibition by the ε subunit (23).…”
mentioning
confidence: 99%
“…The bacterial and chloroplast ATP synthases are equipped with an intrinsic inhibitory subunit ⑀, which strongly suppresses the ATP hydrolysis reaction (2-4). The C-terminal ␣-helical part of the ⑀ subunit has been shown to be critical for this inhibitory function (5). Another regulatory mechanism is known as ADP-inhibition (6).…”
mentioning
confidence: 99%
“…The structure is dynamic, as indicated by cross-linking studies that show that the C-terminal arm of ⑀ undergoes a significant conformational change in response to occupancy of catalytic sites with different nucleotides (41,42). A number of studies with CF 1 have indicated that the ⑀ subunit is likely to exist in conformations similar to those of the EcF 1 enzyme (19,20,28,(43)(44)(45). We therefore propose that the inhibitory action of CF 1 ⑀ results from a direct binding interaction between the C-terminal arm of ⑀ and the central domain of the ␥ subunit, in particular residues within the regulatory domain and the extra loop segment as indicated by these studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the same trypsin-sensitive sites on ␥ as those exposed upon removal of ⑀ from soluble CF 1 become exposed (9,18). At the same time, epitopes on the C terminus of the ⑀ subunit become exposed to antibodies present in the medium (16,19,20), and Lys 109 on ⑀ becomes solventexposed (17). Trypsin cleavage of ␥ in light-energized CF 1 results in uncoupling of ATP synthesis from electron transport (21).…”
mentioning
confidence: 99%